2020
DOI: 10.5599/admet.760
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the octanol-water distribution coefficient of basic compounds by a cationic microemulsion electrokinetic chromatography system

Abstract: <p class="ADMETabstracttext">The octanol-water partition coefficient (P<sub>o/w</sub>), or the octanol-water distribution coefficient (D<sub>o/w</sub>) for ionized compounds, is a key parameter in the drug development process. In a previous work, this parameter was estimated through the retention factor measurements in a sodium dodecyl sulfate (SDS) - microemulsion electrokinetic chromatography (MEEKC) system for acidic compounds. Nonetheless, when ionized basic compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…of the two ME systems has been correlated to two structural descriptors that may have an important influence on their retention: the McGowan volume and the log Po/w. On one hand, it has been demonstrated that the McGowan volume has a very important contribution when the retention of neutral compounds is evaluated in MEEKC systems.On the other hand, good correlations have been observed between log Po/w and the retention of neutral compounds in these two MEEKC systems[6,25]. Correlations are shown in FiguresS2a and S2bof the supplementary information.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…of the two ME systems has been correlated to two structural descriptors that may have an important influence on their retention: the McGowan volume and the log Po/w. On one hand, it has been demonstrated that the McGowan volume has a very important contribution when the retention of neutral compounds is evaluated in MEEKC systems.On the other hand, good correlations have been observed between log Po/w and the retention of neutral compounds in these two MEEKC systems[6,25]. Correlations are shown in FiguresS2a and S2bof the supplementary information.…”
mentioning
confidence: 75%
“…The use of basic or acidic compounds to prepare the buffers does not affect the mobilities obtained, indicating that aggregation of protonated bases is mainly caused by the SDS surfactant. a) Data from [24]; b) Data from [25]; c) Measured in this work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain physicochemical properties of molecules have been recognized as early indicators of potential problems with early drug discovery compounds [ 19 ]. Besides lipophilicity [ 20 ], solubility [ 21 ] and permeability, biomimetic properties such as protein [ 22 ] and phospholipid binding [ 23 ] can be measured at the early stages of the drug discovery process [ 24 ]. The chromatographic technique provides an automated, high throughput and reliable measurement of important properties of the drug discovery compounds [ 25 ] that can be used to estimate later stage in vivo properties of compounds such as the volume of distribution, the unbound volume of distribution [ 26 ] and the drug efficiency [ 27 ].…”
Section: Introductionmentioning
confidence: 99%